2011
DOI: 10.1016/j.curtheres.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Ankaferd Blood Stopper Against Candida albicans

Abstract: The various tests were carried out to investigate antifungal effects of ABS on Candida, but none were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Pellati et al (2009) and Motsei et al (2003) also demonstrated that 18-beta glycyrrhetinic acid, the key components of ABS, is known to possess a strong antifungal effect on the Candida albicans [36,37]. This property can be utilized for preparing various antifungal mouthwashes for the treatment of oral candidiasis and other fungal infections [47][48][49][50][51][52]. Therefore ABS should be tried as an antiplaque and anti-gingivitis agent for the treatment of gingivitis, periodontitis, periapical, periodontal abscess and postoperative infections following periodontal surgery.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Pellati et al (2009) and Motsei et al (2003) also demonstrated that 18-beta glycyrrhetinic acid, the key components of ABS, is known to possess a strong antifungal effect on the Candida albicans [36,37]. This property can be utilized for preparing various antifungal mouthwashes for the treatment of oral candidiasis and other fungal infections [47][48][49][50][51][52]. Therefore ABS should be tried as an antiplaque and anti-gingivitis agent for the treatment of gingivitis, periodontitis, periapical, periodontal abscess and postoperative infections following periodontal surgery.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…ABS is also known to inhibit the growth of various yeast and filamentous fungi. Ciftci et al (2011) assessed the antifungal effect of ABS using a good diffusion agar test and found that ABS has a high antifungal effect against Zygosaccharomyces bailii, Candida albicans, Aspergillus flavus, and Aspergillus parasiticus [47]. Pellati et al (2009) and Motsei et al (2003) also demonstrated that 18-beta glycyrrhetinic acid, the key components of ABS, is known to possess a strong antifungal effect on the Candida albicans [36,37].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
See 3 more Smart Citations